Improving competitiveness of peasant farms in Armenia - Казарян, А. Р. (Scientific Progress & Innovations, 2013)
The level of competitiveness of farms is still low in Armenia because of their small sizes, low level of governmental support, low development of infrastructures, mechanization and other factors. In our opinion, increasing the competitiveness of farms is possible by optimizing their sizes, increasing the availability of credit resources, mechanizing of production, in putting affective systems of insurance and subsidy, etc. otherwise the farms in Armenia will develop with the same low pace.